Faktor-Faktor Yang Berhubungan dengan Pemanfaatan Program Pelayanan Lanjut Usia (Posyandu Lansia) di Wilayah Kerja Puskesmas Sawah Kabupaten Kampar - Meldy Diani (Photon: Jurnal Sain dan Kesehatan, 2022)
Abstract The Achievement of implementation the minimum standard service for elderly in Kampar Regency was still low from 28,478 elderly, only 17,832 (62.6%) who get elderly health services. The implementation of the elderly MSS at the Sawah Public Health Center was ranked the 4th lowest the elderly MSS achievement of the 31 public health centers in Kampar Regency. The purpose of research was to determine the relationship between knowledge, attitudes, family support, and the role of cadres on the elderly service program. This type of research was quantitative with a cross sectional analytical research design. The sampling amounted to 143 peoples. The Collecting data used a questionnaire. The data analysis used univariate, bivariate and multivariate analysis. The results of the research found that there was a relationship between knowledge, attitudes, family support, and the role of cadres on the utilization of Posyandu services for the elderly at the Sawah Public Health Center, Kampar Regency. It can be concluded that public health center must improve health promotion in the form of counseling on the importance of using posyandu for the elderly and advocating for community leaders to increase visits to integrated post service for the elderly. Keywords: Elderly Posyandu, Program, Sawah Public Health Center